Valorization of Cyanophyta by hydrothermal carbonization: Co-production of CO2 adsorbents and fluorescent carbon dots; Journal of the Energy Institute; Vol. 118 - Han Xu; Lili Qian; Wenyu Ma; Yanxin Wang; Dan Fang; Xiao Liu; Chuan Yuan; Bo Zhang; Yingdong Xu; Yamin Hu; Yang Guo; Donghai Xu; et al. (2025, 2025)
Cyanophyta blooms can lead to eutrophication and generate algal toxins. To reduce their environmental risks, hydrothermal carbonization was innovatively applied to simultaneously produce activated carbon (AC) and carbon dots (CDs). AC was further used for CO2 adsorption while CDs were for preparing fluorescent materials. Yields of AC and CDs were investigated under mild conditions of 160–240 °C and 15–240 min. Characterization results show that AC exhibited a large specific surface area of 990 m2 g−1 and pore volume of 1.14 cm3 g−1, contributing to high CO2 adsorption capacities of 3.26 mmol g−1 (0 °C) and 2.06 mmol g−1 (25 °C). Additionally, nitrogen and oxygen self-doping heteroatoms CDs, with a photoluminescence quantum yield of 2.58 %, emitted stable blue fluorescence under the ultraviolet light and were successfully applied to produce invisible ink. This work provides a paradigm for CO2 reduction and high-value material synthesis via the thermochemical conversion of hazardous biomass